Kajian Keberkesanan Bonggol Jalan Dan Bar Melintang (Transverse Bar) Di Jalan Persiaran Gurney, Jalan Sempadan Dan Jalan Persiaran Pekaka - Jamaludin, Mohd Muzamil (Universiti Sains Malaysia, 2006)
The objective of this study is to compare on the effectiveness of road bumps and transverse bars in reducing the speed of various types of vehicles. In order to obtain the speed reduction data, vehicles speed data traveling before and after road bump and transverse bar were collected at various locations in areas with high intensity population such as Gurney Drive, Penang and medium density population such as Nibong Tebal and Parit Buntar. Analyses were then conducted based on various vehicles categories such as cars, motorcycles and lorries to obtain the speed of vehicles traveling before and after the speed bump and transverse bar. The results obtained were then compared with the design specifications in Arahan Teknik (Jalan) Jabatan Kerja Raya.